Factors influencing user behaviour in micromobility sharing systems: A systematic literature review and research directions - Elmashhara, Maher (2022)
In light of the Micromobility Sharing Systems (MSS) boom, specifically bike and scooter sharing, related academic studies have grown accordingly in the last few years. However, contributions are scattered, particularly regarding the knowledge about the user of these systems. This article provides a systematic review of the studied factors influencing MSS user behaviour and offers insights for future research. An inclusive search of the Web of Science and Scopus databases was performed to identify related literature. The final analysis included 203 articles that met the eligibility criteria. The findings were organised into three main groups that aggregate 25 factors influencing MSS user behavioural responses: (i) temporal, spatial and weather-related factors, (ii) system-related factors and (iii) user-related factors. The review uncovered several neglected factors, as well as theoretical and methodological gaps in the literature. Based on that, the study suggests directions for future studies including researching the emotional influences and outcomes of MSS use, considering environmental beliefs and behaviours in the MSS context, examining negative behaviours and negative assessments of MSS use, and consolidating the use of theoretical frameworks.